IRG1/itaconate increases IL-10 release to alleviate mechanical and thermal hypersensitivity in mice after nerve injury - Sun, Qingyu; Hu, Tingting; Zhang, Yurui; Wang, Xiaotong; Liu, Jing; Chen, Wen; Wei, Chao; Liu, Dianxin; Wu, Weihua; Lan, Ting; Ding, Yumeng; Luo, Zhaoli; et al. (Frontiers in Immunology, 2022)
Inflammation plays an important role in the occurrence and development of neuropathic pain. Immune-responsive gene 1 (IRG1) decarboxylates cis-aconitate to produce itaconate in the mitochondria. Itaconate serves as an immunomodulator of macrophages and represses inflammation in infectious diseases. Recently, a study showed that an itaconate derivative inhibits neuroinflammation and reduces chronic pain in mice. However, the function and molecular mechanisms of endogenous itaconate in neuropathic pain have not been fullyelucidated. In this study, the content of itaconate in the ipsilateral spinal cord after nerve-injured mice was detected with mass spectrometry. The Irg1-/- mouse was constructed to determine the role of endogenous itaconate in the chronic constriction nerve injury (CCI) model. The analgesic effect of exogenous itaconate was assessed with intraperitoneal and intrathecal administration in both male and female CCI mice. The spinal application of 4-OI also reduced the evoked responses of wide dynamic range neurons in CCI mice. The potential analgesic mechanism of itaconate was explored through molecular biology experiments and verified in Interleukin (IL)-10-/- mice. We found the levels of itaconate and IRG1 in the spinal cord significantly increased after CCI. Irg1 deficiency aggravated the mechanical and heat hypersensitivity, while the exogenous administration of the itaconate derivative 4-OI alleviated the neuropathic pain in male and female CCI mice. Mechanistically, the treatment of 4-OI increased the level of IL-10 and activates STAT3/β-endorphin pathway in the spinal cord, and the analgesia effect of itaconate was impaired in IL-10-/- mice. Finally, we showed that the upregulation of IL-10 induced by 4-OI was mainly from spinal neurons through Nrf2 pathway. This study demonstrated the analgesic effect of endogenous and exogenous itaconate in the neuropathic pain model, suggesting that the spinal IL-10/STAT3/β-endorphin pathway might mediate the analgesia effect of itaconate.